A Strategic Framework for Promoting Agricultural Marketing and Agribusiness Development in the West Bank, Palestine - Sadeh, Hamdi (Technium Social Sciences Journal, 2025)
The Palestinian agricultural sector which is a part of the national economy that helps in providing food security, rural livelihood, and cultural heritage. However, is still unable to develop as a result of low market efficiency, infrastructural deficiencies, resource limitations, and political constraints. This research provides a strategic framework for the development of agricultural marketing and agribusiness in the West Bank, using qualitative methods like stakeholder interviews, Social Network Analysis (SNA), and Value Chain Analysis (VCA). The framework denotes three main strategies to improve the sector: one of them is the development of regional marketing for supplying the market thereby reduction of costs and increase of profitability, reinvestment in infrastructure for value addition and supply chain resilience, and lastly working with local and international partnerships to get new markets. The technologically advanced applications like blockchain-based supply chains, collective farming, and regulations facilitating the practice of precision irrigation are suggested. Besides, it involves the land tenure reforms, financial inclusion, and gender-responsive initiatives as a way to empower vulnerable groups. Citing the examples of successful export strategies in Vietnam, and Thailand, the research points out the importance of building digital platforms and export-oriented strategies. One of the most important recommendations is the establishment of a Palestinian Agricultural Marketing and Agribusiness Promotion Service (PAMAPS), which is intended to smooth trade, bring in investment, and propel policy reforms. The research, although the existence of conflict and the lack of resources, through digital transformation, sustainable practices, and inclusive policies aims to diminish post-harvest losses and boost productivity, thus positioning the agricultural sector in West Bank as competitive, resilient, and globally integrated.